Referral of the Halocypridina Thaumatocypris (Miocene, Australia) to the Cladocopina (Ostracoda, Halocyprida) - Warne, Mark T.; Jones, Peter J.; Kornicker, Louis S. (Zootaxa, 2006)
B. K. Nadeau in 1955 identified as Thaumatocypris ostracodes from the middle Miocene Glenample Clay of Victoria, southeastern Australia. Nadeau’s collection of Ostracoda from the Glenample Clay was located in the collections of the Museum of Victoria, Melbourne. Examination of that material indicates that the Glenample Clay specimens attributed by Nadeau to Thaumatocypris belong to Polycope sanctacatherinae Whatley & Downing 1983. As a result, it is concluded that Thaumatocypris has not been collected in the Miocene of Australia. Furthermore, in a broader biostratigraphic/palaeobiogeographic context, the result confirms that no member of the Suborder Halocypridina has been reported so far from the Tertiary Period.